Is bird fancier's lung associated with coeliac disease?. Issue 4 (August 1978) - Hendrick, D J; Faux, J A; Anand, B; Piris, J; Marshall, R
Abstract : Precipitin responses to different avian serum antigens occur in bird fancier's lung (BFL) and coeliac disease. Failure to distinguish between them could encourage an erroneous diagnosis of BFL in patients with coeliac disease, and the recent suggestion that these two disorders are strongly associated may be questioned, partly for this reason. In the present study small bowel biopsy specimens were obtained from 12 of a series of 14 patients proved to have BFL by inhalation provocation tests. None was suggestive of coeliac disease. Of a further 61 patients with biopsy-proved coeliac disease, seven were found to be exposed currently and 33 formerly to birds. As a result of clinical evaluation, BFL was considered a possible cause of undue breathlessness reported by three of the current bird fanciers only, and all underwent inhalation provocation tests. One alone gave positive results. We conclude that if a real association does exist between these two disorders, its clinical importance has been greatly exaggerated.